PERKEMBANGAN PERJANJIAN DALAM PRAKTIK PERDAGANGAN (PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF) - Cindawati, Cindawati (Fakultas Syariah, 2016)
Agreement in human life to protect the rights and obligations are balanced. Differences in Islamic Law Perspective: Halal, agreed, able, without coercion, consent and Qobul. While the perspective of Positive Law: agree, capable, certain things, certain circumstances in accordance with Article 1320 of the Civil Code. The equation embracing principle of freedom of contract (al-Hurriyah) Islamic law is based on freedom of contract and volunteerism of each of the parties to a transaction (Q.S.An-Nisa ', 29). Give freedom to every person doing contract as desired, specify its legal consequences are religious teachings. The development of standard agreements in practice must be based on Sharia Principles provide benefits both parties, within the limits of lawful and unlawful, and the limits of public order and contract law, the provisions of Islamic law which is original. Perspective Positive Law: Principles embraced Open, gives the broadest freedom has entered into agreements contain anything, does not violate public order and morality. Rapid trade development followed the model